Collaborater for a Car‐Like Vehicle Driven by a User with Visual Inattention. Issue 1 (8th May 2012) - Chavez, D.; Slawinski, E.; Mut, V.
Abstract This paper proposes a control system applied to a car‐like vehicle driven by a user. The controller is designed to mitigate the negative effects produced by possible visual distractions of this user. In addition, the paper proposes to evaluate the user's visual distraction, defining a vector that has two components: one with respect to the path and the other with respect to the obstacles. These elements can be computed on‐line and are associated with two time delays that produce a similar effect of instability on the motion of the vehicle. The proposed scheme considers the distraction in the design through such delays. Finally, experiments using a car simulator are carried out